Math, asked by Ojhavarun, 1 year ago

3x+2y=4;2x-3y=7 by substitution method

Answers

Answered by Anonymous
49
Hey Mate ✌

Here's your answer friend,

==> 3x + 2y = 4...............[1]

==> 2x - 3y = 7................[2]

From eq(1) we get,

==> y = 4 - 3x/2............[3]

Now by substituting eq(3) in eq(2) we get,

2x -3y = 7

==> 2x - 3[(4 - 3x)/2] = 7

==> 2x + (- 12 + 9x)/2 = 7

==> (4x -12 + 9x)/ 2 = 7

==> 4x - 12 + 9x = 7 X 2

==> 13x - 12 = 14

==> 13x = 14 + 12

==> 13x = 26

==> x = 2

Now by substituting x = 2 in eq (1) we get,

==> 3x + 2y = 4

==> 3(2) + 2y = 4

==> 6 + 2y = 4

==> 2y = 4 - 6

==> 2y = -2

==> y = (-1)

Thus, x = 2 and y = (-1) .

⭐ Hope it helps you ^_^⭐

Answered by Cutiepie93
23
Hello friends!!

Here is your answer :

3x + 2y = 4 \:  \:  \: ......(1)


2x - 3y = 7 \:  \:  \: ......(2)


From eqⁿ (1)

2y = 4 - 3x


y =  \frac{4 - 3x}{2}  \:  \:  \: .....(3)



Putting the value of y in eqⁿ (2)


2x - 3y = 7


2x - 3( \frac{4 - 3x}{2} ) = 7



2x -  \frac{12}{2}  +  \frac{9x}{2} = 7


2x - 6 +  \frac{9x}{2}  = 7



 \frac{4x + 9x}{2}  = 7 + 6


 \frac{13}{2} x = 13


x =  13 \times \frac{2}{13}


x = 2


Putting the value of x in eqⁿ (3)


y =  \frac{4 - 3x}{2}


y =  \frac{4 - 3(2)}{2}


y =  \frac{4 - 6}{2}


y =  \frac{ - 2}{2}


y =  - 1



Therefore, x = 2

y = - 1


Hope it helps you..

☺️☺️☺️☺️

# Be Brainly
Similar questions